Analisis Laporan Keuangan untuk Mengukur Kinerja Keuangan pada PT. Asia Sejahtera Mina Tbk - Resqianti Resqianti; Nurmega Nurmega; Johanis Padang (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine the financial performance pf Pt. Asia Sejahtera Mina Tbk. Using two ratios, namely likuidity and profitability, this study uses a quantitative descriptive method using secondary data analysis in the form of financial reports for the period 2019-2023. Research findings based on likuidity ratio analysis show that the current ratio, quick ratio, and cash ratio are used by researchers to determine whether the company’s likuidity threshold in 2019-2023 fluctuates. And based on the relative profitability analysis, it shows that return on infestment and return on equity also fluctuate